Use of Nanoparticles for the Treatment of Malignant Neoplasm As a Cancer Targeted Drug Delivery System - Gayoor, Mohammad Khan; Yezdani, Umama; Kumar, Ayush; Sadar, Mayur; Rav, Shorabh; Sahu, Lalit (Asian Journal of Pharmaceutical Research and Development, 2019)
The current situation of Malignant Neoplasm is very different it’s the fourth decade and despite much progress has been made in categorizing the environmental causes and cellular and molecular biological basis for this dreaded disease, Malignant Neoplasm commonly known as (Cancer) till now we did not understand the actual difference between the cancer cell and its normal counterpart. If we did not understand we cannot control, eliminate, treat cancer. The human genome sequence and its subsequent improvements in the sequence data are important steps to fully comprehend cancer cell biology. The current recent advances in the understanding of pharmacokinetic & pharmacodynamic behaviour of drug have offered a more rational approach to the development of optimal drug delivery system. The novel drug delivery systems (NDDS) are carriers which maintain the drug concentration in therapeutic range for a longer period of time. Nanotechnology, a new, novel focus of research evolved from the convergence and coalescence of many diverse scientific disciplines which includes Nanomedicine will have an impact on the key challenges in cancer therapy: nanotubes, Nanopores, and nanoparticles are the most promising applications for various Malignant Neoplasm treatments.